2008
DOI: 10.1614/ws-07-189.1
|View full text |Cite
|
Sign up to set email alerts
|

Seed Persistence in the Field May Be Predicted by Laboratory-Controlled Aging

Abstract: Weed management is complicated by the presence of soil seed banks. The complexity of soil–seed interactions means that seed persistence in the field is often difficult to measure, let alone predict. Field trials, although accurate in their context, are time-consuming and expensive to conduct for individual species. Some ex situ techniques for estimating seed life expectancy have been proposed, but these fail to simulate the environmental complexity of the field. Also, it has been questioned whether techniques … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(101 citation statements)
references
References 30 publications
(28 reference statements)
2
98
1
Order By: Relevance
“…Higher temperature during seed development increases seed germinability in many species (Llorens et al 2008). According to Long et al (2008), warm temperature at the time of Parthenium seed production enables the seed once shed to persist in the soil for more than three years, whereas cool temperature permit survival for only 1 -3 years. Toh et al (2011) reported that increased temperature enhances growth of Parthenium, enlarges canopy size and structure and accelerates population growth rate because of the shortened life cycle, supported by Entz &Fowler (1991) in wheat and Pandey et al (2003) in Parthenium.…”
Section: Discussionmentioning
confidence: 99%
“…Higher temperature during seed development increases seed germinability in many species (Llorens et al 2008). According to Long et al (2008), warm temperature at the time of Parthenium seed production enables the seed once shed to persist in the soil for more than three years, whereas cool temperature permit survival for only 1 -3 years. Toh et al (2011) reported that increased temperature enhances growth of Parthenium, enlarges canopy size and structure and accelerates population growth rate because of the shortened life cycle, supported by Entz &Fowler (1991) in wheat and Pandey et al (2003) in Parthenium.…”
Section: Discussionmentioning
confidence: 99%
“…In a variation on the controlled ageing test used in Long et al (2008), seeds were aged in the laboratory to accelerate ageing within a soil environment. Soils were collected from the field trial site and spread in a 10 to 20 mm layer in shallow plastic dishes that were sealed in boxes above a saturated KNO 3 solution, which created an atmosphere of 94.6% RH at 20°C.…”
Section: Soil-specific Accelerated Ageing Test (Ssaat)mentioning
confidence: 99%
“…The decline in germination observed during the controlledageing test indicated the seed should be short lived, i.e. survives less than 3 years in the environment (Long et al 2008;; our model estimated a P 90 of 13.3 days. In other words, 10% of seed is likely to continue to persist in the environment for longer.…”
Section: Controlled Agingmentioning
confidence: 87%
“…Following the comprehensive study performed by Long et al (2008), the CAT P 50 value may be converted into a rough prediction of field persistence. Species with low CAT P 50 (1-10) values tended to have relatively short seed persistence, those with higher P 50 values (>10) had longer persistence.…”
Section: Controlled Agingmentioning
confidence: 99%